Common fisheries policy of the European Union and Turkey’s adoptation process - Çakabey, Anıl (My University, 2005)
Bu tezin yazılmasındaki amaç Avrupa Birligi’nin Ortak Balıkçılık Politikası’nın olusumu, bu olusumun gerekliliginin nasıl ortaya çıktıgı, yasanılan basarı ve basarısızlıkların incelenmesidir. Bu yapılırken Türkiye’nin durumu, üyelik için ne kadar hazır oldugu, konuyla ilgili iç problemleri irdelenmektedir. Avrupa Birligi bilindigi gibi diger uluslararası organizasyonlardan farklı olarak uluslarüstü bir özellik göstermektedir. Bu özelligi ile bir çok alanda düzenlemeler ve yaptırımlar getirmistir, bunlardan biri de Ortak Balıkçılık Politikasıdır. Balıkçılık tarihler boyu hem gelir, hem de bir besin kaynagı olarak görülmüstür. Balıkçılık tarihi, siyasal, sosyal, ekonomik degerleri içersinde barındıran bir alandır ve balıklar ortak bir mal ve miras olarak görüldügünden konu zaman zaman karmasık bir hal almıstır. Bu durum ülkeler arasında savaslara bile neden olmustur. Bu çalısmada, balıkçılıgın ve Avrupa Birligi Balıkçılık Politikası’nın tarihsel gelisimine, uygulamalarına, karsılastırmalı olarak yer yerde olaylardan örnekler vererek deginilmistir. Üç tarafı denizlerle çevrili ülkemizin bu dogal zenginligini nasıl daha verimli ve gelir getiren bir alan haline dönüstürülebilecegi, bu alandaki eksikleri incelenmistir.

The aim of writing this thesis is to investigate the formation of Common Fisheries Policy within the Europe, the necessity of appereance of this formation and to examine the sucess and the failures of it. During this formation, the situation of Turkey, the readiness of it to the membership, and its local problems due to the subject are scrutinized. As it is known, the EU shows a supranational characteristics which is different from the other international organizations. Its peculiarity has brought arrangements and also investments to the areas; one of which is the Common Fisheries Policy. Fisheries has seen both revenue and the source of food throught out the history. The history of fishery is an area which takes in the political, social and economic values. As the fish is seen as common property and a common heredity this subject became complicated time to time. This state also caused wars between the countries. This work has touched to the development of fisheries, the development of Common Fisheries Policy throughout the history, application of it and comparing it by giving examples of the incidents. It is also examined that, our country whose three sides are surrounded by seas would make this natural richness into more productive way and how it would make it more effective area to get more revenue. All the deficiency in this area is also investigated.
Keywords: Avrupa Birliği_Balıkçılık_Ekomomi; Balıkçılık Politikası_Avrupa Birliği